PENGARUH LITERASI KEUANGAN SYARIAH, SOCIAL INFLUENCE, KEMUDAHAN, DAN KEMANFAATAN TERHADAP MINAT PENGGUNAAN E-MONEY SHOPEEPAY - Kiky Ismawati Oktaviani; Mahmudatus Sa’diyah (J-EBI Jurnal Ekonomi dan Bisnis Islam, 2024)
This research examines the influence of sharia financial literacy, social influence, convenience and usefulness factors on interest in using Shopeepay e-money. With advances in technology, it is now easy for people to make transactions using just a smartphone as well as electronic payments such as e-money. This research uses quantitative methods. The sample in this study was generation Z Muslims who used ShopeePay e-money, totaling 96 respondents who were calculated using the ancient rao formula. Questionnaire data collection techniques. Multiple linear regression analysis technique. The results of the research show that sharia financial literacy has a significant positive effect on interest in using ShopeePay e-money, obtained by a value of tcount > ttable, namely 2.259 > 1.6617 with a significance value of less than 0.05 (0.026 < 0.05). Social Influence has a significant positive effect on interest in using ShopeePay e-money, obtained by a value of tcount > ttable, namely 2.218 > 1.6617 with a significance value of less than 0.05 (0.029 < 0.05). Convenience has a significant positive effect on interest in using ShopeePay e-money. The value obtained is tcount > ttable, namely 2.426 > 1.6617 with a significance value of less than 0.05 (0.017 < 0.05). And usefulness also has a significant positive effect on interest in using ShopeePay e-money. The value obtained is tcount > ttable, namely 2.029 > 1.6617 with a significance value of less than 0.05 (0.045 < 0.05).